Malakoplakia with aberrant ALK expression by immunohistochemistry: a case report - Xiao-Ying Zhang; Jun Li; Shui-lian Chen; Ying Li; Hao Wang; Jin-hua He (BMC, 2023)
Abstract Background Malakoplakia is a rare inflammatory disease of the urogenital tract. There have been no reports of malakoplakia expressing anaplastic lymphoma kinase (ALK) to date. Here, we present one case of malakoplakia with aberrant ALK expression by immunohistochemistry and discuss the clinical significance. Case presentation A 65-year-old Chinese woman with a history of diabetes presented with solid masses in the liver and kidney and elevated lesions on the mucosal surface of the colon. Right nephrectomy and partial liver resection were performed. Microscopically, sheets of histiocytes with poor intercellular adhesion were seen, with Michaelis-Gutmann bodies present in both the intracellular and extracellular interstitium. CD10-, CD68-, and CD163-positive cells were present, with Michaelis-Gutmann bodies confirmed by staining with Alcian blue, periodic acid-Schiff (PAS), periodic acid-Schiff with diastase, Von Kossa, and Prussian blue. Aberrant ALK1 and ALK (D5F3) expression was observed in the cytoplasm and nucleus of cells. However, ALK gene mutation was not detected by fluorescence in situ hybridization or whole exome next-generation sequencing. NGS revealed nine individual somatic gene mutations: GOT1L1, GLIS2, SPOUT1, TMEM97, MUC3A, NSD2, SFXN5, ADAD1 and RAD50. The significance of the somatic gene mutations detected in this study is not clear, and the relationship between them and malakoplakia cannot be clarified by existing scientific studies. The pathological diagnosis was malakoplakia with aberrant ALK expression by immunohistochemistry. The antibiotics imipenem and vancomycin were started based on the results of drug sensitivity analysis and the patient was subsequently discharged. She experienced no discomfort during 30 months of follow-up. Conclusion This is the first reported case of malakoplakia with aberrant ALK expression, it should be differentiated from ALK-positive histiocytosis to avoid misdiagnosis.